IMPLEMENTASI MULTIMEDIA DEVELOPMENT LIFE CYCLE PADA APLIKASI MEDIA PEMBELAJARAN UNTUK ANAK TUNAGRAHITA - Ambarwati, Putri; Darmawel, Putri Syifa (Majalah Ilmiah UNIKOM, 2020)
Mental retardation is a condition of intellectual disabilities experienced by children who have abilities below average. Children with intellectual disabilities are difficult to understand the lesson because they have a delay in developing intelligence. Interactive multimedia-based learning media can be used as one solution to become a method in mentally disabled children's learning process. This study aims to build a learning media for mentally disabled children based on interactive multimedia called Edinata, which stands for learning media for children with intellectual disabilities. Edinata is an application to help developmentally disabled children in introducing letters, numbers, surrounding objects, and coloring games. The method used in the development of this interactive multimedia learning media is the Multimedia Development Life Cycle (MDLC), which consists of 6 stages: concept, design, material collecting, assembly, testing, and distribution. In this study, the black box method is used to conduct testing. Based on black-box testing that has been done, all the menus contained in the application can be run properly. Key Words : mental retardation, interactive learning media